Caracterização sociodemográfica, clínica e qualidade de vida de pessoas afetadas pela Hanseníase em município da Baixada Maranhense - CARNEIRO, Cristina Rosângela do Nascimento (2023)
INTRODUCTION: Leprosy is a chronic disease with high infectivity, it causes sequelae that affect the performance of activities, generating stigmas that interfere with the quality of life. The concept of quality of life involves experiences ranging from basic needs to a sense of fulfillment and personal happiness. Brazil is the second country with the highest number of cases in the world, making leprosy a public health problem. OBJECTIVE: To analyze the sociodemographic, clinical, and quality of life characteristics of people affected by leprosy, in a Municipality in Baixada Maranhense. MATERIAL AND METHOD: Descriptive epidemiological study, involving population of individuals aged 18 years or over and were notified as cases of leprosy under follow-up in the Municipality of Pinheiro – MA, in 2022. Data was collected by applying a form - Leprosy Cases, Simplified Neurological Assessment form and the Physical Quality of Life Index in Dermatology, analysis of secondary data taken from the National Disease Notification System (SINAN) forms and medical records. Collection carried out from June 2022 to January 2023. Information typed in the Microsoft Excel® software and analyzed in the EPI-INFO program, version 7. RESULTS: The sample profile was more frequent in males (72.22%), brown color/race (66.67%), high percentages among illiterates (27.78%) and family income between BRL 1,200.00 and 2,400.00 (55.56%). Higher frequency between the multibacillary form (61.11%), zero degree of physical disability (44.44%), people no history of leprosy in the family (72.22%), and disease duration of less than one year (44.44%). The DLQI showed a greater impairment of quality of life in males (76.92%), black (80%) and brown (75%), among the illiterate (100%) and incomplete higher education (100%), in people with family income between BRL 1,200.00 and 2,400.00 (80%). Commitment between the multibacillary (81.82%), degree II (100%), with a family history of leprosy (80%), and disease duration of less than 1 year (87.50%). Only 27.78% of the Score did not show impairment of quality of life. In the evaluation of questions/domains, the results showed that all were affected. The municipality has a very high endemicity parameter, there is impairment in the quality of life of people living with leprosy, there is a need for improvement in epidemiological surveillance actions and financial incentive for research on topics involving neglected diseases, with greater focus on care and health management, especially in the Family Health Strategy.